2013
DOI: 10.3171/2013.6.peds12606
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and limitations of repeat resection for pediatric malignant neuroepithelial tumors

Abstract: Object Maximized tumor resection and minimized surgical morbidity are extremely important in the treatment of children with malignant neuroepithelial tumors. However, the indications for repeat surgery for these tumors remain unclear. The present study investigated the clinical significance and limitations of repeat resection for these tumors. Methods This study included 61 consecutive pediatric patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…38 In contrast, another study revealed that the risk of dissemination was not increased even if surgical resection of gliomas with CUSA was repeated more than twice. 39 Therefore, the risk of dissemination might depend on the tumor characteristics. No case of dissemination has been reported after ADPJ usage, but reduction of the actual number of dispersed cells is important to assure the safety of ADPJ.…”
Section: Discussionmentioning
confidence: 99%
“…38 In contrast, another study revealed that the risk of dissemination was not increased even if surgical resection of gliomas with CUSA was repeated more than twice. 39 Therefore, the risk of dissemination might depend on the tumor characteristics. No case of dissemination has been reported after ADPJ usage, but reduction of the actual number of dispersed cells is important to assure the safety of ADPJ.…”
Section: Discussionmentioning
confidence: 99%